Elucidating the Role of the T Cell Receptor Repertoire in Myelodysplastic Neoplasms and Acute Myeloid Leukemia - Georgios Petros Barakos; Vasileios Georgoulis; Epameinondas Koumpis; Eleftheria Hatzimichael (Diseases)
T cells, as integral components of the adaptive immune system, recognize diverse antigens through unique T cell receptors (TCRs). To achieve this, during T cell maturation, the thymus generates a wide repertoire of TCRs. This is essential for understanding cancer evolution, progression, and the efficacy of immunotherapies. Myelodysplastic neoplasms (MDS) and acute myeloid leukemia (AML) are hematological neoplasms that are characterized by immune evasion mechanisms, with immunotherapy giving only modest results thus far. Our review of TCR repertoire dynamics in these diseases reveals distinct patterns: MDS patients show increased TCR clonality with disease progression, while AML exhibits varied TCR signatures depending on disease stage and treatment response. Understanding these patterns has important clinical implications, as TCR repertoire metrics may serve as potential biomarkers for disease progression and treatment response, particularly in the context of immunotherapy and stem cell transplantation. These insights could guide patient stratification and treatment selection, ultimately improving therapeutic outcomes in MDS and AML.